Concussion in the National Hockey League: a systematic review of the literature - Andrew W Kuhn; Gary S Solomon (Concussion, 2015)
Players in the National Hockey League (NHL) are often sidelined by injuries, including concussion. The acute, intermediate and long-term effects of repetitive head trauma remain a concern of many. ...